Molecular dynamics studies of impulse driven reactions in molecules and molecular clusters. (July 2015) - Gatchell, M; Delaunay, R; Stockett, M H; Rousseau, P; Domaracka, A; Wang, Y; Chen, T; Adoui, L; Alcamí, M; Martín, F; Schmidt, H T; Hubert, B A; et al.
Synopsis: We have used molecular dynamics methods to study collisions between atoms and molecules or molecular clusters. We find that these collisions may yield highly reactive molecular fragments and efficient intracluster covalent bond-forming reactions in the cluster. There is a good agreement between our simulations and various experimental results.